PRODUCTION OPTIMIZATION FOR AGENTS OF DIFFERING WORK RATES - HIGGINS, PETER M. (The ANZIAM journal, 2024)
We devise schemes for producing, in the least possible time, p identical objects with n agents that work at differing speeds. This involves halting the process to transfer production across agent types. For the case of two types of agent, we construct schemes based on the Euclidean algorithm that seeks to minimize the number of pauses in production.